Being Muslim in a Secular World: Indonesian Families in Washington DC Area - Husin, Asna (Studia Islamika, 2019)
Indonesian Muslims in Washington DC and the surrounding states of Maryland and Virginia are an important Indonesian community in the United States. They are one of a few Indonesian American communities with a Muslim majority. We survey its birth and assess the early Indonesian and Indonesian Muslim presence in America and their arrival routes. We then examine the lack of Indonesian interest to immigrate to this continent until very recently. Our study draws upon scholarly research on Indonesian-Dutch connections and the early Indonesian experience in the United States. Data about the Indonesian Muslim Association in America (IMAAM) mosque are derived from interviews with over two hundred leaders and members of the community (jamā‘ah). This includes in-depth interviews with forty-six selected individuals, and observation of the masjid activities over a year (April 2017 – June 2018) forms an integral part of this explorative research.